As interfaces dos Conselhos Escolares do Sistema Municipal de Ensino de João Pessoa - Lelis, Lúcia de Fátima Gomes de (2010)
The management policies of education and school management policies for the 20 (twenty) years have gained a prominent role in discussions, research and other educational and social public spaces. The education reform that occurred during this period recognized the school as a privileged space for realization of the educational policies and by extension the policies of school management. In contemporary reform in primary education in Brazil reflects the influences of national and international contexts. In Brazil, the context of educational reforms occurred between the paradox of implementing the management approach of public management on the one hand and societal approach to public management, on the other. The paradigm of public management does not apply managerial mechanisms of democratic management as a mean of social control of education policies. The societal approach of public administration encompasses education as a social right and uses the instruments of democratic management approach-participatory approach as a mean of guaranteeing the social rights established in the Federal Constitution (FC) 1988 and other supplementary laws. Thus, school boards are instruments of democratization of public education and guarantee of social rights. Therefore, this research has as its object of study, the school boards of the Municipal School of Joao Pessoa, whose purpose is to analyze its performance. This study used a qualitative approach to the application of exploratory and descriptive levels. The exploratory level is justified in light of the unveiling of more explicit about the role of school councils in teaching units that comprise the sample of this research. The descriptive level complements the first characterizing the phenomenon under analysis. For collecting and analyzing data, we applied the following techniques of qualitative research: observation, semi-structured interview and the method of content analysis. We interviewed 17 (seventeen) members of school councils. Investigation showed that the manner of operation of school boards has this gap between what is proposed and diagnosed the distortions in their way of functioning in the classroom. It was found that the boards were turned into wards of the school governing bodies, so they need to make urgent changes to assume its central role, which is to contribute to the promotion of decentralization policies, sharing of activities and / or skills in different doings of the educational process. The school councils as instruments of autonomy of school management, need to work collaboratively for the effectiveness to constitutional principle, with the democratization of public education for all.